The relations between 'babysigning', child vocabulary and maternal mind-mindedness. Issue 12 (2nd December 2017) - Zammit, Maria; Atkinson, Susan
ABSTRACT: Babysign classes are increasingly popular across the UK. Benefits are said to include increasing child vocabulary, reducing frustration, and improving parent–child relations. A further relationship between the use of babysign and maternal mind-mindedness (MM) has been suggested. It was hypothesized here that parents choosing babysign classes would describe their child using more mind-minded comments than those attending other toddler classes and that their children would have greater language skills. The MM scores of 34 mother–child dyads attending parent–toddler activities were measured using Meins et al.'s (2012) research protocol. Mothers also completed a communicative checklist for language and gesture use and understanding. Results indicate that mothers who choose to use babysign describe their children with significantly more mind-minded attributes, but language skills do not differ between the two groups of children. This supports the hypothesis that mothers using babysign would show more MM than mothers not using babysign.